Nonverbal communication in the classroom (Journal of Parents and Teachers, 2014)
Non-verbal communication is always present as part of the emotional relationship between students and teachers in the interactions in educative contexts. However, in our cultural tradition, body, space and voice language, have gone unnoticed, but emotional non-verbal expressions make learning and personal maturing easier.
Keywords: teachers’ training; non-verbal communication; voice; emotions transmission.